2018
DOI: 10.1002/hbm.24227
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic white matter in multiple sclerosis: A combined diffusion‐tensor imaging and quantitative susceptibility mapping study

Abstract: Thalamic white matter (WM) injury in multiple sclerosis (MS) remains relatively poorly understood. Combining multiple imaging modalities, sensitive to different tissue properties, may aid in further characterizing thalamic damage. Forty-five MS patients and 17 demographically-matched healthy controls (HC) were scanned with 3T MRI to obtain quantitative measures of diffusivity and magnetic susceptibility. Participants underwent cognitive evaluation with the Brief International Cognitive Assessment for Multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The mild trend we observed towards decreased R2* along several of the NAWM tracts, which can result from iron loss and demyelination, is congruent with this. Taken together, our QSM results are consistent with prior imaging and pathology studies that have found evidence of decreased iron content in NAWM [18, 30, 38, 39]. Such depletion could have important implications as iron plays an important role in maintaining cellular functions such as metabolism and lipid synthesis [40, 41].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mild trend we observed towards decreased R2* along several of the NAWM tracts, which can result from iron loss and demyelination, is congruent with this. Taken together, our QSM results are consistent with prior imaging and pathology studies that have found evidence of decreased iron content in NAWM [18, 30, 38, 39]. Such depletion could have important implications as iron plays an important role in maintaining cellular functions such as metabolism and lipid synthesis [40, 41].…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, QS may vary depending on the relative white matter location (i.e., periventricular, deep, subcortical, and perilesional) as well as within different brain regions (i.e., centrum semiovale versus corpus callosum). Along these lines, a separate study focusing on thalamic WM found decreased QS in MS compared to HC [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Brain iron levels are known to be disturbed in multiple sclerosis (MS) (Filippi et al, 2019; Hagemeier, Geurts, & Zivadinov, 2012; Zecca, Youdim, Riederer, Connor, & Crichton, 2004). Most studies reported increased iron concentrations in the deep gray matter (DGM) (Stankiewicz, Neema, & Ceccarelli, 2014) and around plaques (Craelius, Migdal, Luessenhop, Sugar, & Mihalakis, 1982), and reduced iron concentrations within lesions (Haider et al, 2014; Kutzelnigg et al, 2005; Laule et al, 2013; Yao et al, 2012; Yao et al, 2014), in the normal‐appearing white matter (WM) (Hametner et al, 2013; Paling et al, 2012; Popescu et al, 2017; Yu et al, 2018), and in the thalamus (Bergsland et al, 2018; Burgetova et al, 2017; Khalil et al, 2015; Louapre et al, 2017; Pontillo et al, 2019; Schweser et al, 2018; Uddin, Lebel, Seres, Blevins, & Wilman, 2016; Zivadinov et al, 2018). The literature considers findings of increased region‐average iron concentrations as evidence for iron influx (Bergsland et al, 2019; Ndayisaba, Kaindlstorfer, & Wenning, 2019; Williams, Buchheit, Berman, & LeVine, 2012), whereas it is less clear how to interpret reduced iron concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Mangeat et al ( 2015 ) used two-dimensional independent components analysis of magnetization transfer, cortical thickness, B 0 orientation, and R2* to extract information about the fraction of myelin in white matter. Bergsland et al ( 2018 ) used QS and diffusion metrics to perform separate univariate statistical analyses of thalamic white matter tracts and used non-parametric correlation analysis to combine these measures and quantify their association with clinical disease metrics.…”
Section: Introductionmentioning
confidence: 99%